The Strategies of Sufi Discourse in Fostering Communal Immunity: The Sufi as a Nomadic Subject - Tayeb Bouchoir (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2023)
This paper examines the strategies that Sufis adopted during covid-19 crisis which are journey and seclusion: two strategies that characterize Sufi’s behaviour. Using qualitative research, this paper argues that though the policies enacted in the time of covid-19 has led humanity into herd immunity in which bodies have been subjected to a set of improvised political decisions, Sufi bodies are immune bodies by nature, as they are characterized by an inner immunity that makes of them either in a state of journey or in a state of seclusion. Drawing from Rosi Braidotti (2011) ’s poststructuralist notion of nomadic subjectivity, this paper also states that the Sufi can be seen as a ‘nomadic subject’ able to experience not only physical journey shaping the move from one territory to another but also a kind of non-physical journey pertaining to spiritual ascension shaping the path to God. As a result, Sufi discourse is a site for fostering communal immunity where individuals are provided with strategies to transcend not only the pandemic as a temporary disaster but also the problems of life as well as the challenges menacing humankind.